Augmented Reality-Based Board Game for Learning English for Junior High School Students - Handy Putra Maslan; Erdhi Widyarto Nugroho; FX Hendra Prasetya (Soegijapranata Catholic University, 2022)
English is the language used by all countries as the main communication tool. By understanding English, young people can have the opportunity to work abroad and gain more knowledge and better job opportunities. But education in Indonesia and the willingness of young people to learn is still low, young people tend to prefer to play games rather than learn. Therefore, a game made with Augmented Reality technology was combined with a Board Game called the game